2019
DOI: 10.1021/acs.langmuir.9b00043
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Role of Monoolein in Fluidity and Dynamical Response of a Mixed Cationic Lipid Bilayer

Abstract: The maintenance of cell membrane fluidity is of critical importance for various cellular functions. At lower temperatures when membrane fluidity decreases, plants and cyanobacteria react by introducing unsaturation in the lipids, so that the membranes return to a more fluidic state. To probe how introduction of unsaturation leads to reduced membrane fluidity, a model cationic lipid dioctadecyldimethylammonium bromide (DODAB) has been chosen, and the effects of an unsaturated lipid monoolein (MO) on the structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“… , In this time-resolved measurement, a short pulse is given for the electronic excitation of the fluorophore molecules and the fluorescence spectrum of the optically excited chromophore red shifts in time as the surrounding solvent molecules reorient themselves surrounding the solute probe molecules to establish a new, excited charge distribution state. Therefore, the dynamics of the overall solvent response is described in terms of solvation correlation function [ C ( t )], which serves as a better descriptor of the environmental response due to the coupled dynamics of the lipid molecules and their surrounding water molecules . It is true that C153 does not contain any hydrophobic anchor, but still its hydrophobicity is more compared to the commonly used varieties of other coumarin dyes.…”
Section: Resultsmentioning
confidence: 99%
“… , In this time-resolved measurement, a short pulse is given for the electronic excitation of the fluorophore molecules and the fluorescence spectrum of the optically excited chromophore red shifts in time as the surrounding solvent molecules reorient themselves surrounding the solute probe molecules to establish a new, excited charge distribution state. Therefore, the dynamics of the overall solvent response is described in terms of solvation correlation function [ C ( t )], which serves as a better descriptor of the environmental response due to the coupled dynamics of the lipid molecules and their surrounding water molecules . It is true that C153 does not contain any hydrophobic anchor, but still its hydrophobicity is more compared to the commonly used varieties of other coumarin dyes.…”
Section: Resultsmentioning
confidence: 99%
“…Dioctadecyldimethylammonium bromide (DODAB) is a double chained cationic lipid (Fig. 1) which forms a lamellar structure in aqueous solution analogous to biological membranes and has been widely investigated due to their membrane mimetic properties [31][32][33][34][35][36]. Various recent studies have shown the usefulness of DODAB membranes for a number of biomedical applications such as antimicrobials [37][38], drug/vaccine delivery [39][40][41], and gene/DNA transfection [42].…”
Section: Fig1 Chemical Structures Of the Dodab Lipid And Caffeinementioning
confidence: 99%
“…These motions occur in a wide range of time scales ranging from vibrations at ∼fs to flip flop motions which take a few hours, and over a wide variety of length scales, from molecular rotations at a few Ås to the macroscopic deformation of the vesicles at the micrometer scale. To investigate these motions, various experimental methods have been used, such as dynamic light scattering (Hassan et al, 2015;Sharma et al, 2020), fluorescence spectroscopy (Machán and Hof, 2010;Singh et al, 2019), electron paramagnetic resonance (McConnell and Kornberg, 1971), nuclear magnetic resonance (Perlo et al, 2011), quasielastic neutron scattering (Busch et al, 2010;Armstrong et al, 2011;Sharma et al, 2015aSharma et al, , 2017aDubey et al, 2018;Sharma and Mukhopadhyay, 2018), neutron spin echo (Boggara et al, 2010;Lee et al, 2010;Woodka et al, 2012;Nickels et al, 2015). Each method has limited accessible temporal and spatial regimes.…”
Section: Introductionmentioning
confidence: 99%